Marine Heatwaves Characteristics in the Barents Sea Based on High Resolution Satellite Data (1982–2020) - Mohamed, Bayoumy; Nilsen, Frank; Skogseth, Ragnheid (Frontiers in Marine Science, 2022)
Marine heatwaves (MHWs) can potentially alter ocean ecosystems with far-reaching ecological and socio-economic consequences. This study investigates the spatiotemporal evolution of the main MHW characteristics in the Barents Sea using high-resolution (0.25° × 0.25°) daily Sea Surface Temperature (SST) data from 1982 to 2020. The results reveal that the Barents Sea has experienced accelerated warming and several more MHWs in recent decades. Since 2004, an amplified increasing SST trend was observed across the entire Barents Sea, with a spatially averaged SST trend of 0.25 ± 0.18°C/decade and 0.58 ± 0.21°C/decade for the northern and southern Barents Sea, respectively. The annual mean MHW frequency, days, and duration over the entire Barents Sea increased by, respectively, 62, 73, and 31% from the pre- to the post-2004 period. More than half of all MHW days occurred in the last decade (2011–2020). The most intense MHW event occurred in summer 2016, which was also the warmest year during the study period. In general, the annual mean MHW frequency was relatively high in the northern Barents Sea, while the intensity and duration were higher in the southern Barents Sea. The highest annual MHW intensity and duration were observed in 2016, 2013, and 2020, respectively, while the highest annual MHW frequency was found in 2016. For the entire Barents Sea, the annual MHW frequency and duration increased significantly (p < 0.05) over the whole study period, with a trend of, respectively, 1.0 ± 0.4 events/decade, which is a doubling of the global average, and 2.4 ± 1.3 days/decade. In terms of the influence of climate variability on MHW characteristics, our findings revealed that the Eastern Atlantic Pattern (EAP) plays a significant role in controlling MHW characteristics, whereas the North Atlantic Oscillation (NAO) has no significant relationship. Sea ice concentrations were found to have a significant negative correlation with MHW characteristics. Strong positive correlations were observed between SST, surface air temperature, and MHW frequency, implying that as global warming continues, we can expect continued rising in MHW frequencies and days in the Barents Sea with huge implications for the ocean ecosystem.